SPATIAL DATA MODELS: SPATIAL DATA MODELS - Ivanov, Sabin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Spatial data represents the shape, location, and spatial relationships of geographic features to other features. The form represents the geometry of the objects, the location is described by a list of x, y coordinates of discrete points of the objects, and the spatial connections (topological information) of the geographical objects determine the interaction between them. Spatial (coordinate) information can also include time-related data.